A comparison of computerized adaptive testing and fixed-length short forms for the Prosthetic Limb Users Survey of Mobility (PLUS-MTM). (October 2018) - Amtmann, Dagmar; Bamer, Alyssa M; Kim, Jiseon; Bocell, Fraser; Chung, Hyewon; Park, Ryoungsun; Salem, Rana; Hafner, Brian J
Background: New health status instruments can be administered by computerized adaptive test or short forms. The Prosthetic Limb Users Survey of Mobility (PLUS-M TM ) is a self-report measure of mobility for prosthesis users with lower limb loss. This study used the PLUS-M to examine advantages and disadvantages of computerized adaptive test and short forms. Objectives: To compare scores obtained from computerized adaptive test to scores obtained from fixed-length short forms (7-item and 12-item) in order to provide guidance to researchers and clinicians on how to select the best form of administration for different uses. Study design: Cross-sectional, observational study. Methods: Individuals with lower limb loss completed the PLUS-M by computerized adaptive test and short forms. Administration time, correlations between the scores, and standard errors were compared. Results: Scores and standard errors from the computerized adaptive test, 7-item short form, and 12-item short form were highly correlated and all forms of administration were efficient. Computerized adaptive test required less time to administer than either paper or electronic short forms; however, time savings were minimal compared to the 7-item short form. Conclusion: Results indicate that the PLUS-M computerized adaptive test is most efficient, and differences in scores between administration methods are minimal. The main advantage of the computerized adaptive test was more reliable scores at higher levels of mobility compared to short forms. Clinical relevance: Health-related item banks, like the Prosthetic Limb Users Survey of Mobility (PLUS-M TM ), can be administered by computerized adaptive testing (CAT) or as fixed-length short forms (SFs). Results of this study will help clinicians and researchers decide whether they should invest in a CAT administration system or whether SFs are more appropriate.